THE INFLUENCE OF ENDORSEMENT AND INFLUENCER CREDIBILITY ON PURCHASE INTENTION MEDIATED BY ADVERTISING REMINDERS AT FIT-S911 BEAUTY CENTER BEAUTY CLINIC - Inggrid Trisnawaty Wibowo; Bernard T. Widjaja; Saparso (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Beauty business is any type of business related to beauty products or services to enhance appearance. Similarly, it causes increasing market needs and interests. Today's beauty clinics are increasingly fierce competition, where appearance is one of the main focuses of everyone, thus forcing beauty clinic owners to compete to use different business strategies to maintain the beauty clinics they have. The need for beauty is useful for increasing consumer confidence. Data were obtained through questionnaires distributed randomly. The analysis technique used is SEM using AMOS software version 5. From the results of the analysis, it is obtained that Endorsment and Influencer Credibility affect purchase intention, Endorsment and Influencer Credibility affect advertising reminders and Endorsment and Influencer Credibility positively significantly affect purchase intention mediated by advertising reminders.